Building A Sharia Entrepreneurial Ecosystem Through Halal Value Chain for MSMEs - Riziqiyah, Metiya Fatikhatur; Zahro, Umi Chabibatus; Setyorini, Ririn (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
Independent entrepreneurs promise certain material benefits if the entrepreneur succeeds in running the business. Sharia business and economic patterns are still a big challenge and opportunity to be implemented in Indonesia. Creating a sharia-based entrepreneurial ecosystem is very important for MSME players to be aware of so that they can optimize the business they run according to Islamic law and God's provisions. This halal value chain is a sharia economic sector that plays an important role in economic progress in Indonesia. However, for Indonesia, halal is an economic potential that has not been exploited optimally. One thing that supports building a sharia entrepreneurial ecosystem and is able to increase sales value is by carrying out halal certification on the products it makes. The Community-Based Empowerment Partner in this activity is UMKM Wijayakusuma Sejati assisted by Jatisawit Village Bumiayu Brebes. The aim of this service is (1) to provide partner knowledge in creating a sharia-based entrepreneurial ecosystem and mentality, (2) to provide production and marketing knowledge, (3) to provide business capital management competence, (4) to provide knowledge about production and marketing, management competence business capital, bookkeeping and preparation of financial reports, and (5) facilitating halal certification for Wijayakusuma Sejati MSME products. This training is needed for traders to create a sharia entrepreneurial mentality and halal certification based on the halal value chain so they are able to manage their business well, create a brand image for their products, and increase sales significantly.